New probiotics (Lactobacillus plantarum and Saccharomyces cerevisiae) supplemented to fermented rice straw-based rations on digestibility and rumen characteristics in vitro - Marlida, Yetti; Harnentis, Harnentis; Nur, Yuliaty Shafan; Ardani, Laily Rinda (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research was arranged to explore the effect of supplementation of a combination of Lactobacillus plantarum and Saccharomyces cerevisiae as a new probiotic in fermented rice straw-based rations on in vitro digestibility and ruminal characteristics. Materials and Methods: A randomized group design with 3 types of treatment and 4 replications as a group was used in this study. A probiotic inoculum containing L. plantarum and S. cerevisiae with 1 × 1010 colony-forming unit (CFU)/ml. Treatments were followed by: P1 = complete rations without probiotics (control), P2 = P1 supplemented 0.5% probiotics, and P3 = P1 supplemented 1% probiotics. Substrate complete rations were based on the fermented rice straw and concentrate (60%:40%). Parameters of digestibility and rumen fermentation products were determined after 48 h of incubation. Results: Probiotics supplemented with fermented rice straw-based rations significantly increased (p < 0.05) digestibility and rumen characteristics in vitro. Supplementation with 1% probiotics (P3) produces the highest digestibility compared to other treatments: in-vitro dry matter digestibility (IVDMD) (55%), in-vitro organic matter digestibility (IVOMD) (58.28%), in-vitro crude protein digestibility (IVCPD) (84.42%), in-vitro acid detergent fiber digestibility (IVADFD) (53.99%), in-vitro neutral detergent fiber digestibility (IVNDFD) (58.39%), and in-vitro cellulose digestibility (IVCLD) (67.12%). Rumen pH (6.76–6.80) did not change significantly (p > 0.05) due to supplemented probiotics. Probiotic supplementation in rations significantly (p < 0.05) increased the content of NH3 and total volatile fatty acid (VFA). Supplementation with 1% probiotic (P3) showed the highest concentration of NH3 (26.56 mg/100 ml) and was also followed by the total VFA (115.75 mM) compared to the control (22.59 mg/100 ml and 103.00 mM, respectively). Conclusion: Supplementation of 1% probiotics (combination of L. plantarum and S. cerevisiae) containing 1 × 1010 CFU/ml in fermented rice straw-based rations increases nutrient digestibility, that is, IVDMD, IVOMD, IVCPD, IVADFD, IVNDFD, and IVCLD, and also increases rumen fermentation, which is the concentration of NH3 and total VFA. J. Adv. Vet. Anim. Res., 10(1): 96–102, March 2023 http://doi.org/10.5455/javar.2023.j657